South Atlantic Omega Validation. Volume 3. Appendices M-Q. - Watt,T. M.; Bailie,G. J.; Sutphen,M. (1983)
Appendixes: Omega Signal Coverage at 13.6 kHz in South Atlantic Region; Diurnal Variations in LOP Error at 13.6 kHz in South Atlantic Region; LOP Error Statistics at 13.6 kHz in South Atlantic Region; Fix Errors at 13.6 kHz in South Atlantic Region; Results of NOSC Airborne Measurements along Transmitter Radials at 13.6 kHz. See also Volume 1, AD-A181 508.